ABORSI DALAM TINJAUAN ETIKAKESEHATAN, PERSPEKTIF ISLAM, DAN HUKUM DI INDONESIA - Listiyana, Anik (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2012)
Abortion is still a controversial problem in Indonesian society recently. Statistical data which are revealed by National Board for family Planning Coordination show that around 2.000.000 cases of abortion practiced in Indonesia every year. The debate on its legality to be practiced, particularly the four schools of sect, agree to put abortion as an unlawful practice. Therefore, abortion generally is a cruel action, against humanity valuesand it also against law and religious tenets. However, regardless all those aspects, its legal status should be studied specifically and deeply because it is not a single action .This sort of action has various kinds of action based on its conditional consideration. This writing aims at discussing abortion by looking at Indonesian legal regulation through criminal law and health regulation.